Active transform fault zone at the fringe of the Dead Sea Basin. Issue 7 (22nd July 2015) - Wetzler, Nadav; Sagy, Amir; Sagy, Yael; Nahmias, Yoav; Lyakhovsky, Vladimir
Abstract: The evolution of an asymmetric basin at the edge of a pull‐apart structure is studied using geophysical observations and mechanical modeling. A new seismic analysis of the northern edge of the Dead Sea basin indicates recent subsidence, folding and oblique faulting along the Jericho strike‐slip fault; a main segment of the Dead Sea Transform fault. The subvertical fault trace crosses the entire sedimentary sequence typically branching in the shallow subsurface. The seismic analysis reveals the three‐dimensional structure of the area as an asymmetrical basin bordered on the east and on the west by long monoclinic folds. The thickness of the sedimentary fill varies from 1.4 km near the present lake shores to a few hundreds of meters about 10 km northward. The subsidence is partitioned between a vertical component of slip along the Jericho Fault and the simultaneously active monoclines bordering the basin. We present a model and simulations that reconstruct the present basin structure in the uppermost part of the crust and demonstrates the generation of flexures along the basin margins without horizontal shortening. We show that the basin asymmetry and the association of folds and fault can be explained as a long‐term ductile response of the sediments to local subsidence. The asymmetry along the basin is a consequence of a later vertical displacement component on a pre‐existing strike‐slip fault. Our analysis points to ongoing northward propagation of the Dead Sea basin and provides an explanation for the structural asymmetry of the basin margins. Key Points: Jericho fault is an active plate boundary transform branched in the subsurface Strike‐slip along the Jericho fault is associated with subsidence and folding Viscous flow, driven by subsidence, controls the regional structure shape